2020
DOI: 10.3390/s20205851
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality with 360-Video Storytelling in Cultural Heritage: Study of Presence, Engagement, and Immersion

Abstract: This paper presents a combined subjective and objective evaluation of an application mixing interactive virtual reality (VR) experience with 360° storytelling. The hypothesis that the modern immersive archaeological VR application presenting cultural heritage from a submerged site would sustain high levels of presence, immersion, and general engagement was leveraged in the investigation of the user experience with both the subjective (questionnaires) and the objective (neurophysiological recording of the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 59 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…They articulated a negative view that such characteristics masked the statistically significant differences in the results. Filip Škola et al [ 9 ] measured the EEG response of users who were experiencing a 360° immersive VR application program, and reported that a high beta band substantially increased in the later phase of EEG measurement. They deduced the participants’ VR experience raised their cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They articulated a negative view that such characteristics masked the statistically significant differences in the results. Filip Škola et al [ 9 ] measured the EEG response of users who were experiencing a 360° immersive VR application program, and reported that a high beta band substantially increased in the later phase of EEG measurement. They deduced the participants’ VR experience raised their cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…VR has been combined with mobile brain/body imaging (MoBI), which synchronously records movement and brain dynamics during active exploration of the virtual environment [ 33 ]. Furthermore, prior work has utilized EEG techniques when performing evaluations of virtual reality environments [ 8 , 9 , 11 ].…”
Section: Application Of Vr-eeg In Architectural Researchmentioning
confidence: 99%
See 3 more Smart Citations